Three-dimensional localization under severely obstructed NLOS environment - Zhu XIAO; Jie CHEN; Dong WANG; Xiao-hong LI; Ren-fa LI (Tongxin xuebao)
In the severely obstructed NLOS(non-line-of-sight)environment,obstacles between the UN(unknown node)and RS(reference station)made the DP(direct path)undetectable.It greatly restricted the application of wireless localization method.A three-dimensional localization scheme,which utilized the distance and orientation information of single-bounce signal,was proposed to evade the DP blocking effect in three-dimensional NLOS environment.Within the proposed localization scheme,three-dimensional spatial location relationship among the RS,UN and scatterers was proven.Anoptimization algorithm based on least mean square was proposed and the mathematical solution to the position relationship was derived.Furthermore,the performance of algorithm is studied by using RMSE(root mean-square error)analysis.Through Monte-Carlo simulations,how distance and orientation deviation of three-dimensional localization frame affect performance of algorithms is examined.It is also demonstrated that the analytical results closely match the simulations,which verifies the effectiveness of the proposed three-dimensional NLOS localization algorithm.